Visions of the End in Medieval Spain. Catalogue of Illustrated Beatus Commentaries on the Apocalypse and Study of the Geneva Beatus - Williams, John (Amsterdam University Press, 2017)
Never before have all twenty-nine illustrated copies of the Beatus Commentaries on the Apocalypse been brought together for comparative analysis in a single volume. John Williams, renowned expert on the Commentaries, offers here his updated considerations on the material, revising and summing up a lifetime of study on these strikingly illuminated manuscripts. Dating from the early to central Middle Ages, the Spanish phenomenon of the Commentary on the Apocalypse responded to differing monastic needs within the shifting context of the Middle Ages. The volume also presents an in-depth study of the recently discovered Geneva Beatus. One of only three Commentaries written outside the Iberian Peninsula, this manuscript closely follows a Spanish model but was written in a Beneventan script and painted in a style dramatically different from the original.